2023
DOI: 10.3389/fendo.2023.1224418
|View full text |Cite
|
Sign up to set email alerts
|

In vivo retinal imaging is associated with cognitive decline, blood-brain barrier disruption and neuroinflammation in type 2 diabetic mice

May Majimbi,
Samuel McLenachan,
Michael Nesbit
et al.

Abstract: IntroductionType 2 diabetes (T2D) is associated with chronic inflammation and neurovascular changes that lead to functional impairment and atrophy in neural-derived tissue. A reduction in retinal thickness is an early indicator of diabetic retinopathy (DR), with progressive loss of neuroglia corresponding to DR severity. The brain undergoes similar pathophysiological events as the retina, which contribute to T2D-related cognitive decline.MethodsThis study explored the relationship between retinal thinning and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
2
3
0
Order By: Relevance
“…Bogdanov et al [73] describe neurodegeneration as early as 2 months of age -an age when mice just develop hyperglycaemia. However, even though they show a slightly reduced retinal thickness at this early age, they do not show a loss of neuronal cells over the course of ageing from 2 to 6 months, which one would expect to see in a progressive disease like DR. More consistent with our findings, many other studies report no change in retinal layer thickness in db/db mice at approximately 3 months of age, but an onset of retinal thinning and neuronal cell loss at approximately 6-7 months of age [37,44,49]. We found significantly reduced cone numbers, which is in line with other studies that found predominant cone photoreceptor dysfunction in early-stage DR in zebrafish [77] and humans [78,79].…”
Section: Early Functional But Late Onset Of Morphological Changes Of ...supporting
confidence: 93%
See 4 more Smart Citations
“…Bogdanov et al [73] describe neurodegeneration as early as 2 months of age -an age when mice just develop hyperglycaemia. However, even though they show a slightly reduced retinal thickness at this early age, they do not show a loss of neuronal cells over the course of ageing from 2 to 6 months, which one would expect to see in a progressive disease like DR. More consistent with our findings, many other studies report no change in retinal layer thickness in db/db mice at approximately 3 months of age, but an onset of retinal thinning and neuronal cell loss at approximately 6-7 months of age [37,44,49]. We found significantly reduced cone numbers, which is in line with other studies that found predominant cone photoreceptor dysfunction in early-stage DR in zebrafish [77] and humans [78,79].…”
Section: Early Functional But Late Onset Of Morphological Changes Of ...supporting
confidence: 93%
“…This alings with reports that BRB breakdown and increased apoptosis occur in older db/ db mice [44,45]. Similarily, while microglial activation was observed in mice aged 6-9 months, we detected proinflammatory microglial signatures in 6-month-old db/ db mice before major cellular architecture changes, consistent with other studies [37,49]. However, we detected typical pro-inflammatory microglial signatures in cells isolated from retinae of 6-months-old db/db mice similar to earlier reports [71], thus, before major changes in their cellular architecture occurred, which is supported by the results of other studies [72].…”
Section: Early Functional But Late Onset Of Morphological Changes Of ...supporting
confidence: 93%
See 3 more Smart Citations